Pengembangan Modul Cerita Fabel Bermuatan Nilai-Nilai Pancasila Berbasis Flipbook - Woro Wisudawati; Aida Sumardi (Departement of Mathematics Education, 2023)
This research is motivated by the problems and obstacles experienced by students, namely difficulties in making and imagining in making fable stories. This research will develop Flipbook-based modules in Indonesian language subjects with Fable story text material. The development of this digital module contains. Pancasila values which aims to educate students through moral and social values on the. Pancasila precepts. This research aims to produce digital-based learning media to facilitate learning. The research procedure uses the Research and Development (R&D) method by applying the ADDIE development model which consists of: 1) Analysis, 2) Design, 3) Production Development, 4) Implementation, and 5) Evaluation. The data obtained in this study were obtained using data collection techniques in the form of observations, interviews, material expert and media expert assessments and student response questionnaires to determine the feasibility of digital modules that have been developed. The results of this study indicate that the module of fable story text with Pancasila values based on flipbook obtained the assessment criteria very feasible to be used in learning. This can be seen based on the assessment of media experts with a feasibility percentage of 98% and the assessment of material experts with a feasibility percentage of 97.50%. Meanwhile, the feasibility assessment of the small class trial student response obtained a feasibility percentage of 96.34% and the large class trial assessment obtained a feasibility percentage of 96.47%. The fable story module with Pancasila values has been declared feasible and can be used by teachers and seventh grade students in Indonesian language learning.